2013
DOI: 10.4172/2324-8599.1000118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of In-vivo Application of Cold Atmospheric Plasma on Corneal Wound Healing in New Zealand White Rabbits

Abstract: Cold Atmospheric Plasma (CAP) has been shown to influence tissue wound healing but little is known about the impact of CAP on healthy corneal tissues and their ability to respond to injuries. The objective of this study is to examine the effect of CAP on wound healing after corneal epithelial and basement membrane ablation in New Zealand white rabbits. The rabbits were assigned into three groups. Ten Rabbits from two groups underwent a 6 mm corneal ablation to the right eyes. After ablation, five rabbits in gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…According to their findings, the short-term application of CAP (for 0.5–5 min) could act as an effective and rapid ocular disinfectant for bacteria and fungi without significant damage to the ocular cells and tissues [ 15 ]. In another study, Alhabshan et al (2013) examined the effect of CAP on wound healing in animal models after the corneal epithelial and basement membrane ablation [ 16 ]. They showed that CAP application to the cornea led neither to any evident adverse effects such as scar formation nor to any corneal wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…According to their findings, the short-term application of CAP (for 0.5–5 min) could act as an effective and rapid ocular disinfectant for bacteria and fungi without significant damage to the ocular cells and tissues [ 15 ]. In another study, Alhabshan et al (2013) examined the effect of CAP on wound healing in animal models after the corneal epithelial and basement membrane ablation [ 16 ]. They showed that CAP application to the cornea led neither to any evident adverse effects such as scar formation nor to any corneal wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Even though a gentle disinfection of eye surfaces by CAP was demonstrated several years ago [323], plasma application in ophthalmology is a subject of little research so far. It has been repeatedly demonstrated in some studies in vitro and in first animal experiments, that CAP is effective to inactivate microorganisms without harmful effects on the cornea [324][325][326][327][328]. In a case series including four patients with therapy-resistant corneal ulcers, the clinical potential of CAP to treat infections as well as ulcerations of the cornea was demonstrated [329].…”
Section: Other Prospective Fieldsmentioning
confidence: 93%
“…Furthermore, in chronic wounds important processes relying on radicals are impaired and can be re-stimulated by increasing intracellular concentrations of reactive species (1). Corneas treated for up to 5 min did not show histopathological changes in studies using different devices (15,23,45,69,70). The rate of corneal epithelization in rabbits was not affected by the application of CAP for 2 min (69).…”
Section: Future Researchmentioning
confidence: 99%